2012
DOI: 10.4100/jhse.2012.7.proc1.06
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Albanian female volleyball player with anthropometric, performance and haematological parameters

Abstract: Bozo D, Lleshi E. Comparison of Albanian female volleyball player with anthropometric, performance and haematological parameters. J. Hum. Sport Exerc. Vol. 7, No. Proc1, pp. S41-S50, 2012. The purpose of this study was to investigate and compare, on a set of basic anthropometric characteristics, specific volleyball performance indicators and a number of haematological parameters, between elite and nonelite female volleyball players in Albania. A total of 39 subjects were assesses and analyzed for three sets of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…The fat component of our study participants (16.4%), determined by the skinfold measurements, is close to the lowest values, reported both for the highskilled (14.9-28.9%) and college-level (13.99-25.6%) female players (Bozo and Lleshi 2012;Carvajal et al 2012;Buśko 2012). The thickness of skinfolds might indicate differences regarding the development of subcutaneous fat layer for examined players compared to highly qualified athletes.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The fat component of our study participants (16.4%), determined by the skinfold measurements, is close to the lowest values, reported both for the highskilled (14.9-28.9%) and college-level (13.99-25.6%) female players (Bozo and Lleshi 2012;Carvajal et al 2012;Buśko 2012). The thickness of skinfolds might indicate differences regarding the development of subcutaneous fat layer for examined players compared to highly qualified athletes.…”
Section: Discussionsupporting
confidence: 72%
“…Therefore, body mass observed among study participants corresponds to average values of top-level athletes and above average values of college players. The BMI of study participants (20.83) is comparable to those of other college players (20.0-22.5) and lower than BMI of elite players (22.0-23.2) (Bozo and Lleshi 2012;Buśko 2012;Carvajal et al 2012Carvajal et al , 2015. The larger values of BMI of the top-level players could be the result of higher development of skeletal muscles.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Although female players in senior teams achieve higher values of body height [5,[50][51][52][53], it should be assumed that the tested female athletes will achieve slightly higher values for this feature in subsequent years. It should also be pointed out that the greater body height of female volleyball players is largely the result of morphological selection [25,[54][55][56]. Comparison of examined female athletes with their non-training peers showed that their body height is definitely higher [57].…”
Section: Discussionmentioning
confidence: 96%